Phenotype and genotype of muscle ryanodine receptor rhabdomyolysis‐myalgia syndrome. (29th December 2017) - Witting, N.; Laforêt, P.; Voermans, N. C.; Roux‐Buisson, N.; Bompaire, F.; Rendu, J.; Duno, M.; Feillet, F.; Kamsteeg, E.‐J.; Poulsen, N. S.; Dahlqvist, J. R.; Romero, N. B.; et al.
Abstract : Objectives: Rhabdomyolysis and myalgia are common conditions, and mutation in the ryanodine receptor 1 gene ( RYR1 ) is suggested to be a common cause. Due to the large size of RYR1, however, sequencing has not been widely accessible before the recent advent of next‐generation sequencing technology and limited phenotypic descriptions are therefore available. Material & Methods: We present the medical history, clinical and ancillary findings of patients with RYR1 mutations and rhabdomyolysis and myalgia identified in Denmark, France and The Netherlands. Results: Twenty‐two patients with recurrent rhabdomyolysis (CK > 10 000) or myalgia with hyperCKemia (>1.5 × ULN) and a RYR1 mutation were identified. One had mild wasting of the quadriceps muscle, but none had fixed weakness. Symptoms varied from being restricted to intense exercise to limiting ADL function. One patient developed transient kidney failure during rhabdomyolysis. Two received immunosuppressants on suspicion of myositis. None had episodes of malignant hyperthermia. Muscle biopsies were normal, but CT/MRI showed muscle hypertrophy in most. Delay from first symptom to diagnosis was 12 years on average. Fifteen different dominantly inherited mutations were identified. Ten were previously described as pathogenic and 5 were novel, but rare/absent from the background population, and predicted to be pathogenic by in silico analyses. Ten of the mutations were reported to give malignant hyperthermia susceptibility. Conclusion: Mutations in RYR1 should be considered as a significant cause of rhabdomyolysis and myalgia syndrome in patients with the characteristic combination of rhabdomyolysis, myalgia and cramps, creatine kinase elevation, no weakness and often muscle hypertrophy.